Resiliensi Budaya Tradisional Dugderan Dalam Arus Perubahan Sosial Di Kota Semarang - Nova Putri Ramadhan; Dhani Hafizh Raditya; Milatun Nazibah; Ahmad Fauzan Baihaqi (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2025)
The Dugderan tradition is a cultural heritage of Semarang City that is held every year before the month of Ramadan, combining religious values with local cultural expressions. This study examines the transformation of Dugderan from a sacred tradition into a popular cultural festival in the context of modernisation, as well as how this tradition continues to reflect the multicultural identity of Semarang society. Using historical and participatory observation methods, this study traces the historical roots of Dugderan since the 19th century as a response to social fragmentation caused by the colonial policy of ‘divide and rule,’ which later evolved into a symbol of social cohesion and the emergence of the creative economy. Warak Ngendog, the festival's main icon, reflects the acculturation of Javanese, Arab, and Chinese cultures, as well as local wisdom passed down from generation to generation. Findings indicate that despite commercialisation, values of togetherness, tolerance, and cultural identity persist in the Dugderan celebration. However, religious and traditional values are gradually being overshadowed by entertainment and economic orientations. This study underscores Dugderan's role as a space for cultural dialogue, tourism promotion, and cultural preservation amid ongoing globalisation, while emphasising the need for a balanced approach between visual-commercial aspects and the historical, educational, and spiritual values inherent in the tradition.